The Impact of the COVID-19 Pandemic on Food Security at the Household Level: Cross-Sectional Survey in Jakarta and Depok, Indonesia - Syafiq, Ahmad; Fikawati, Sandra (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study aimed to describe when the effects of the pandemic on food security started to be felt by families in Jakarta (urban area) and Depok (semi-urban area). A cross-sectional survey was conducted among 517 respondents. Data were collected using an online questionnaire. The study revealed that effects of economic decline, reduced purchasing power, and increased food prices occurred early during the pandemic. Those living in semi-urban areas were affected earlier than those living in urban areas. However, more semi-urban families perceived that they were prepared to face food shortage during the pandemic. It is recommended to consider these results for public health nutrition program in food security and disaster.